Neuroinflammation as a Therapeutic Target for Mitigating the Long-Term Consequences of Acute Organophosphate Intoxication - Andrew, Peter M.; Lein, Pamela J. (Frontiers in Pharmacology, 2021)
Acute intoxication with organophosphates (OPs) can cause a potentially fatal cholinergic crisis characterized by peripheral parasympathomimetic symptoms and seizures that rapidly progress to status epilepticus (SE). While current therapeutic countermeasures for acute OP intoxication significantly improve the chances of survival when administered promptly, they are insufficient for protecting individuals from chronic neurologic outcomes such as cognitive deficits, affective disorders, and acquired epilepsy. Neuroinflammation is posited to contribute to the pathogenesis of these long-term neurologic sequelae. In this review, we summarize what is currently known regarding the progression of neuroinflammatory responses after acute OP intoxication, drawing parallels to other models of SE. We also discuss studies in which neuroinflammation was targeted following OP-induced SE, and explain possible reasons why such therapeutic interventions have inconsistently and only partially improved long-term outcomes. Finally, we suggest future directions for the development of therapeutic strategies that target neuroinflammation to mitigate the neurologic sequelae of acute OP intoxication.